1994
DOI: 10.1073/pnas.91.25.11998
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2-sensitive, sleep-promoting zone defined in the ventral surface of the rostral basal forebrain.

Abstract: The site of action for the sleep-promoting effect of prostaglandin (PG) D2 was extensively examined in the brain of adult male rats (n = 231). PGD2 was administered at 100 pmol/0.2 pI per min for 6 hr (2300-0500 hr) through chronically implanted microdialysis probes or infusion cannulae. Among the administrations of PGD2 by dialysis probes (n = 176), only those (n = 8) to a ventro-rostral part of the basal forebrain by the probes implanted on the midline consistently increased slow-wave sleep (SWS), by 51 ± 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
94
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 27 publications
4
94
0
Order By: Relevance
“…In the late 1970s, Hayaishi et al (14) found large amounts of PGDS in the brains of rat and other mammals, including humans. PGD 2 circulates in the ventricular system, subarachnoid space, and extracellular spaces of the brain and interacts with receptors on the ventromedial surface of the rostral basal forebrain to initiate the signal to let the brain sleep (15). PGDS is a member of the lipocalin superfamily composed of various secretory lipophilic ligandcarrier proteins (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…In the late 1970s, Hayaishi et al (14) found large amounts of PGDS in the brains of rat and other mammals, including humans. PGD 2 circulates in the ventricular system, subarachnoid space, and extracellular spaces of the brain and interacts with receptors on the ventromedial surface of the rostral basal forebrain to initiate the signal to let the brain sleep (15). PGDS is a member of the lipocalin superfamily composed of various secretory lipophilic ligandcarrier proteins (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…1). In brief, PGD 2 infused into the subarachnoid space underlying the rostral basal forebrain was effective in inducing sleep but not when infused into most parts of the brain parenchyma of rats (2). The amount of PGD 2 -induced sleep was reduced by pretreatment with KF17837, the specific adenosine A 2A receptor antagonist, in a dose-dependent manner (3).…”
mentioning
confidence: 94%
“…It was previously observed that somatosensory stimulation could elicit bursting activity in the septum [30][31][32][33]. Further the septal neurons are sensitive to pain stimulation as noted by Dutar et al, that majority of septohippocamal neurons in rats are activated by noxious stimuli [18].…”
Section: Discussionmentioning
confidence: 91%